Conceptual development in secondary education: thoughts on electromagnetism / Pensamento teórico na educação básica: reflexões acerca do eletromagnetismo - Martins Fontes, Daniel Trugillo (2019)
It is well known that electromagnetism is not completely understood by students. This paper presents a brief review of different resources found in the research literature to promote students’ conceptual development in electromagnetism. Then it discusses a fundamental concern for planning of teaching approaches to this topic. This theoretical research goes towards enhancing our understanding for planning concrete works in teaching electromagnetism. The hypothesis is that in order to promote students’ theoretical understanding, teachers should let pupils to active engage in the learning process. We use Davydov (1998) as a theoretical basis for motivating this hypothesis.